THE COMPLEXITY OF AFRICAN AMERICAN IDENTITY AT THE INTERSECTION OF SPAIN, FRANCE, AND AN INCIPIENT UNITED STATES - Escobar-Rivera, Emma (Young Scholars Grinchenko – Seton International Journal, 2026)
This article examines the construction and contestation of African American identity through the lens of historical memory, emphasizing the interconnected roles of Spain, France, and the early United States. Drawing on the concept of historical memory as a socially constructed narrative that shapes collective and national identity, the study argues that processes of remembering and erasure have profoundly influenced both the recognition of African American contributions and broader definitions of American belonging. It situates contemporary political efforts to narrow national identity through policies, legal decisions, and the suppression of Black history within a longer tradition of selective historical narration. The author highlights the marginalization of Spain’s role in the American Revolution and its intersection with the underrepresentation of African Americans. Through a detailed case study of Jane Henderson Bronner, a descendant of an enslaved woman freed through then Governor of Louisiana Bernardo de Gálvez’ intervention, the paper illustrates how personal genealogies expose the transnational and multiracial foundations of the United States. This encounter reveals the entanglement of memory, identity, and recognition across time and space. Ultimately, the article argues that African American identity cannot be fully understood within a purely national framework. Instead, it emerges at the intersection of Atlantic histories, shaped by colonial alliances, slavery, and the politics of memory. By recovering overlooked narratives, the study calls for a more inclusive understanding of American identity that acknowledges its global, multilingual, and multicultural origins.